Pengaruh Pelatihan, Pengembangan karir dan Motivasi terhadap Kinerja Pegawai pada PT.PLN UP3 Sidoarjo - Kyki Veronica Anggraeni; Kumara Adji Kusuma; Rifdah Abadiyah; Sumartik Sumartik (Universitas Respati Indonesia, 2024)
Abstract The aim of this research is to identify, analyze and show the impact of training, career development and motivation on employee performance at PT. PLN UP3 Sidoarjo. This research uses quantitative research techniques. Types of primary data sources. This research used 95 respondents from a sample of PT employees. PLN UP3 Sidoarjo. The analysis technique uses multiple linear regression analysis, classical assumptions, partial test (t test), simultaneous test (f test) and coefficient of determination which are the types of hypothesis testing used in this research data analysis. Data processing in this study used the Statistical Program for Social Science (SPSS) version 26. The results obtained in this study explain that the training variable has a positive and significant effect on employee performance, the career development variable has a positive and significant effect on employee performance, and work motivation has an effect positive and significant on employee performance at PT. PLN UP3 Sidoarjo. The study results from this research have implications that focus on trainer qualifications, level of satisfaction, initiative and creativity, showing that creative employees must be able to innovate in finding new opportunities, doing new things, taking ideas from things around them, having a broad outlook.